Executive Committee Minutes 2015-03-05 - Academic Senate:::::::::
Agenda amended and approved. CFA Report. Minutes 2/19/15 – Approved. Appointment of representative for Academic Programs on International Programs, Theresa Alfaro Velcamp approved. Vice Chair Report. Textbook Alternative Pilot report for the Senate. Revision to Computer Science Major and Minor for the consent calendar. Provost report - M. Barnard for A. Rogerson. Statewide Senator Report. Vice President of Administration and Finance Report – J. Wenrick for L. Furukawa-Schlereth. Associated Students Report. Report on the Educational Experience Enhancement Awards. Vice President of Student Affairs Report. Resolution in Support of AS-3197-14, The Need for a Comprehensive California State University Policy on Academic Freedom approved for Senate agenda. EPC Report. Ex Com rep to the SEC Report. Discussion about Emeritus Dinner. Senate agenda approved.